2018
DOI: 10.1007/s00268-018-4835-z
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Capacity to Meet Lancet Commission on Global Surgery Indicators in the Federal Capital Territory, Abuja, Nigeria

Abstract: Background This is a baseline assessment of surgical capacity in the Federal Capital Territory (FCT), in preparation for the creation of a National Surgical, Obstetric, Anesthesia, and Nursing Plan. Methods In October 2017, all 10 of the 11 secondary hospitals in FCT that provide surgical and/or obstetric care were surveyed using a modified World Health Organization Hospital Assessment Tool and a qualitative semi‐structured hospital interview tool of the medical Director (MdD). This project received approval f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The survey conducted in Rwanda found that availability of ketamine and propofol was comparable at around 80%, while thiopental and inhalational agents such as halothane, isoflurane or sevoflurane were available at only about half of the hospitals. These barriers to anaesthesia care identified in this study have been identified previously in different contexts, and this research supports those findings [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The survey conducted in Rwanda found that availability of ketamine and propofol was comparable at around 80%, while thiopental and inhalational agents such as halothane, isoflurane or sevoflurane were available at only about half of the hospitals. These barriers to anaesthesia care identified in this study have been identified previously in different contexts, and this research supports those findings [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…Research has shown that consistent access to electricity and running water remains problematic across SSA, and that availability of oxygen and functional anaesthetic machines is generally low [6][7][8][9][10][11][12][13][14][15][16][17][18]. Essential medicines, such as local or general anaesthetic agents, remain in low supply [6,9,17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the Federal Capital Territory, more than 80% of individuals can reach a hospital with surgical capacity within 2 hours; however, only 50% of those facilities regularly perform laparotomies, and only 40% were staffed by board-certified general surgeons. 80 In more rural regions, the majority of surgical care is performed by general practitioners, and the capacity for elective cancer surgery that requires general anesthesia is quite limited. 81 These data are derived from small, survey-based publications.…”
Section: Access To Treatment Of Recognized Diseasementioning
confidence: 99%
“…To globally report these indicators to the World Bank, a su ciently detailed, sustainable, and cost-effective methodology to achieve timely data collection is necessary. Current efforts to collect LCoGS indicator data rely on top-down approaches, requiring involvement of Ministries of Health, national healthcare informatics and database management, and hospital directors interested in population metrics extrapolated from grassroots levels of care, i.e., clinical settings (5,(10)(11)(12)(13)(14). Although top-down methods enable collection of large volume data, incomplete documentation, fragmented data sources, and exclusion of small hospitals during national data sampling may compromise the accuracy and generalizability of results.…”
Section: Introductionmentioning
confidence: 99%